Implementasi Pembelajaran Berbasis Kearifan Lokal Untuk Anak Usia Dini - Triana Putri; Idawati, Sulis (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2025)
Early childhood is a golden period in child development, where character formation, moral values, and love for culture can be effectively instilled, but the development of the times marked by technological advances and globalization poses a great challenge to efforts to preserve local culture, especially for early childhood. Therefore, preserving local culture in early childhood is a strategic step to maintain the nation's identity. This process can be done through the introduction of local culture in a creative and adaptive manner, such as using culture-based digital media, educational games, and cultural integration in school learning, to achieve this goal, of course, a learning design that is optimally designed to help the learning or preservation of culture for early childhood is needed. The method used in this study is a qualitative approach with a case study in kindergarten that applies this concept. The results of the study show that the application of learning based on local wisdom is able to increase children's involvement, creativity, and understanding of the surrounding environment.